Optimalisasi Wisata Kampung Batik Semarang Sebagai Permukiman Yang Berbasis Sejarah - Santi Widiastuti; Jennie Kusumaningrum; Lies Handrijaningsih (Universitas Sains dan Teknologi Komputer, 2023)
Having been a center for batik activities in the past but experiencing suspended animation in 1970, the condition of the batik village after independence actually experienced a dark period including the title of being a slum village, unsafe because it was a den of criminals and always flooded. Kampung batik is known as an ancient village, whose formation coincided with the history of the city of semarang, its fate experienced ups and downs. However, in 1980, batik craftsmen attempted to revive semarang batik production, although it was not yet optimal due to capital constraints and inadequate human resources in terms of skills. Starting from the concerns that occurred in this historic settlement, the semarang city government carried out the revitalization of the batik village in 2005 and experienced rapid progress until the enactment of regional regulation (perda) no. 14 of 2011 concerning the establishment of batik villages as cultural heritage through the establishment of a thematic village program. The research method is qualitative research with historical methods, which includes heuristics (collecting sources), criticism, interpretation, and writing down facts. The data collection techniques used were interviews, observation and document study. The results of the research can be concluded that batik villages with cultural potential and through community empowerment have become one of the batik producing areas as well as cities with cultural tourism destinations in central java province.